2013
DOI: 10.1128/jvi.00637-13
|View full text |Cite
|
Sign up to set email alerts
|

Frog Virus 3 Open Reading Frame 97R Localizes to the Endoplasmic Reticulum and Induces Nuclear Invaginations

Abstract: Frog virus 3 (FV3) is the type species of the genus Ranavirus, family Iridoviridae. The genome of FV3 is 105,903 bases in length and encodes 97 open reading frames (ORFs). The FV3 ORF 97R contains a B-cell lymphoma 2 (Bcl-2) homology 1 (BH1) domain and has sequence similarity to the myeloid cell leukemia-1 (Mcl-1) protein, suggesting a potential role in apoptosis. To begin to understand the role of 97R, we characterized 97R through immunofluorescence and mutagenesis. Here we demonstrated that 97R localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Western blotting was performed against Tet2, Arginase 1, IκBα, Erk1/ 2, phospho-Erk1/2, Jun, phospho-cJun, and β-actin and immunofluorescence against Tet2 using standard techniques [26,27]. Antibodies and conditions are described in the Supplementary Methods.…”
Section: Western Blots and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed against Tet2, Arginase 1, IκBα, Erk1/ 2, phospho-Erk1/2, Jun, phospho-cJun, and β-actin and immunofluorescence against Tet2 using standard techniques [26,27]. Antibodies and conditions are described in the Supplementary Methods.…”
Section: Western Blots and Immunofluorescencementioning
confidence: 99%
“…Immunofluorescence. Cells were plated on coverslips and fixed in 3.7% paraformaldehyde (Bioshop) as previously described [27]. A Tet2 antibody (S-13, Santa Cruz) was used at 1:50 and cells were mounted with Vectashield Mounting Medium with DAPI (Vector Laboratories, Burlington, ON, Canada).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…For localization studies, it is much easier to use mammalian cell lines, where a variety of intracellular organelle markers exist. In addition, we have used BGMK cells in the past to localize a variety of FV3 genes, and have found that the localization in BGMK cells mimics the localization in amphibian cell lines [30,31]. It is noteworthy that BGMK cells are infectible by FV3 when the cells are incubated at 30 °C [32].…”
Section: Discussionmentioning
confidence: 99%
“…Many vBcl-2 orthologues, including the first viral Bcl-2 orthologue found, adenovirus E1B 19K, though without an obvious hydrophobic C-terminal region, are closely associated with intracellular membranes, the ER and nuclear envelope [ 86 ] and the association with membranes is required for its function [ 87 ]. Frog virus 3 Bcl-2 orthologue 97R localises to the ER and deletion of the C-terminal 29 residues inactivates the protein [ 88 ]. The African swine fever virus Bcl-2 orthologue A179L, is closely associated with viral factories, and though it lacks an obvious TM region, it is associated with the ER and mitochondrial membranes.…”
Section: Membrane Interactionsmentioning
confidence: 99%